A phase II trial of low-dose estradiol in postmenopausal women with advanced breast cancer and acquired resistance to aromatase inhibition. Issue 18 (December 2015) - Zucchini, G.; Armstrong, A.C.; Wardley, A.M.; Wilson, G.; Misra, V.; Seif, M.; Ryder, W.D.; Cope, J.; Blowers, E.; Howell, A.; Palmieri, C.; Howell, S.J.
Abstract: Background: High-dose oestrogen (HDE) is effective but toxic in postmenopausal women with advanced breast cancer (ABC). Prolonged oestrogen deprivation sensitises BC cell lines to estrogen and we hypothesised that third-generation aromatase inhibitors (AIs) would sensitise BCs to low-dose estradiol (LDE). Methods: A single-arm phase II study of LDE (2 mg estradiol valerate daily) in postmenopausal women with estrogen receptor-positive (ER+) ABC. The primary end-point was clinical benefit (CB) rate. If LDE was ineffective, HDE was offered. If LDE was effective, retreatment with the pre-LDE AI was offered on progression. Results: Twenty-one patients were recruited before the trial was closed early due to slow accrual; 19 were assessable for efficacy and toxicity. CB was seen in 5 in 19 patients (26%; 95% confidence interval 9.1–51.2%), all with prolonged SD (median duration 16.8 months; range 11.0–29.6). Treatment was discontinued for toxicity in 4 in 19 patients (21%) and 8 in 11 women without hysterectomy experienced vaginal bleeding (VB). After primary LDE failure, three patients received HDE and one achieved a partial response (PR). Following CB on LDE, four patients restarted pre-LDE AI and three achieved CB including one PR. Those with CB to LDE had a significantly longer duration of first-line endocrine therapy for ABC than those without (54.9 versus 16.8 months; p < 0.01) Conclusion: LDE is an effective endocrine option in women with evidence of prolonged sensitivity to AI therapy. LDE is reasonably well tolerated although VB is an issue. Re-challenge with the pre-LDE AI following progression confirms re-sensitisation as a true phenomenon.